KUALITAS PAPAN KOMPOSIT PLASTIK BERDASARKAN RASIO LIMBAH PLASTIK POLIPROPILENA (PP) DENGAN CAMPURAN SERBUK KAYU SENGON (Paraserianthes falcataria L.I.C. Nielsen) DAN SEKAM PADI (Oryza sativa) - Ayuningtyas, Ika Nurwidya; Dayadi, Irvin (JURNAL ATOMIK, 2023)
The need for wood and plastic products is increasing, it is necessary to optimize the utilization of waste by processing it into plastic composite boards. This study aims to determine the best composition with raw materials of sengon wood powder (Paraserianthes falcataria L.I.C Nielsen) and rice husk powder (Oryza sativa) as filler with a ratio of 50% : 50% and polyprophylene plastic (PP) as a matrix. This treatment uses 3 compositions, P1 (40 % PP : 60 % SS) P2 (50% PP: 50% SS), and P3 (60% PP: 40 % SS ) was hot pressed with a pressure of 30 bar for 20 minutes at a temperature of 180°C with 3 replications for each treatment. The best result was obtained in the P3 (60 % PP : 40 % SS) with an average density value of 0.83 g/cm3, moisture content 1.52%, water absorption 32.16%, thickness swelling 9.34%, MoE 4,057.85 N/mm2, MoR 42.39 N/mm2 and IBS 0.21 N/mm2 Some test results have met plastic composite board standards according to JIS Particle Board A 5908-2003, JIS Plastic Board A 5741-2006 and SNI Plastic Board SNI 8154-2015.